Explanation:
Step 1: Solve the first part
A: 66 + k + 10
B: y^2
C: s + 49
D: 58 +c + 100
E: 62 * x
F: 29 - v
G: 7 / k
H: w + 3
I: t * 45
J: c * 3
K: 9 + w
L: 93 / y
Step 2: Solve the second part
A: (3.6 * t) + (3.6 * 4.6) = 4
3.6t + 16.56 - 16.56 = 4 - 16.56
3.6t / 3.6 = -12.56 / 3.6
t = -3.4888...
B: 2.6 = (6 * c) + (6 * -3.7)
2.6 + 22.2 = 6c - 22.2 + 22.2
24.8 / 6 = 6c / 6
4.1333... = c
C: (4 * -1.8) + (4 * -p) = -2.4
-7.2 - 4p + 7.2 = -2.4 + 7.2
-4p / -4 = 4.8 / -4
p = -1.2
D: (8 * z) + (8 * -3.1) + 6 = 3z + 5
8z - 24.8 + 6 - 3z = 3z + 5 - 3z
5z - 18.8 + 18.8 = 5 + 18.8
5z / 5 = 23.8 / 5
z = 4.76